Additive manufacturing in South Africa: building on the foundations - Campbell, R.I.; de Beer, D.J.; Pei, E. (Rapid prototyping journal, 2011)
Purpose - In a previous Rapid Prototyping Journal paper, the authors reviewed the first decade of rapid prototyping (RP) use within the Republic of South Africa (RSA). The paper analysed its strengths, weaknesses, opportunities and threats, and proposed a "road map" for future development. Much has happened in the intervening years since that article was published and this paper seeks to update readers on the current situation in RSA. In particular, it reports the extensive development of research in the field of RP and additive manufacturing (AM).Design methodology approach - The paper uses a literature review approach combined with reflective analysis to distill the most important developments within the RP community in RSA since 2004. These are compared to the previous road map to ascertain if there are any required actions that have been overlooked or any additional lessons that have been learnt.Findings - The paper shows that there has been good progress against the previous road map and that current plans should remain in place with the addition of a greater educational dimension.Practical implications - This paper provides readers with an overview of important RP AM developments in the RSA. The analysis from this paper will aid RSA academics, industrialists and government agencies to assess their performance and to plan for their future roles within the RP community.Originality value - As with the previous paper, this paper provides a useful model for other countries to follow since it demonstrates both good practice but also the need to learn from past experience.